Design analysis to achieve green/eco school building design typology for Malaysia - Denan, Zuraini; Mazlan, Muhammad Afiq Helmi; Abdul Majid, Noor Hanita; Sanusi, Aliyah Nur Zafirah (Malaysian Institute of Planners, 2018)
Ever since the first establishment of the public school (primary and secondary school) in Malaysia, the building design for most of the schools is almost the same until now. Public school for primary and secondary education is based on a standard layout designed by the Malaysian Public Works Department. Evolution of varieties education system employed by the schools does not affect the physical design of school. The emergence of awareness on sustainability and promotion towards green way of life has made it crucial for designer to rethink the best design for school in enhancing its environment that could be the “third teacher” to the pupils. The research attempt to explore design criteria of green school in Malaysia based on the critical elements of green initiatives. Recommendation of green/eco school design will be presented based on site and building planning, climate and green technology application